2013
DOI: 10.1073/pnas.1221292110
|View full text |Cite
|
Sign up to set email alerts
|

Extensive changes in DNA methylation are associated with expression of mutant huntingtin

Abstract: The earliest stages of Huntington disease are marked by changes in gene expression that are caused in an indirect and poorly understood manner by polyglutamine expansions in the huntingtin (HTT) protein. To explore the hypothesis that DNA methylation may be altered in cells expressing mutated HTT, we use reduced representation bisulfite sequencing (RRBS) to map sites of DNA methylation in cells carrying either wild-type or mutant HTT. We find that a large fraction of the genes that change in expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 71 publications
2
130
0
1
Order By: Relevance
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
“…Based on prior observations by us and others suggesting that (1) HCP genes and LCP genes were regulated differently 13,20,21 and (2) the effects of promoter and gene body methylation diverged, 22,23 we analyzed these scenarios separately. We identified genes that were up-or down-regulated by nerve damage and harbored dDMCs in their promoter or gene body.…”
Section: Genic Ddmcs Altered By Spinal Nerve Ligationmentioning
confidence: 99%
“…1). Even though DNA methylation is the most studied epigenetic mechanism to date, epigenetic changes in terms of DNA methylation in HD are just beginning to be explored [44]. If DNA methylation is altered in HD it could affect many different aspects of gene expression because it is a highly conserved process.…”
Section: Epigenetic Modifications In Hdmentioning
confidence: 99%
“…Altered DNA methylation has recently been found in HD patients and HD transgenic mice [44][45][46]. Interestingly, Ng et al [44] showed that the promoter regions of the Ap-1, Sox2, Pax6, and Nes genes are highly methylated, and that expression levels of these genes are significantly reduced.…”
Section: Epigenetic Modifications In Hdmentioning
confidence: 99%
See 1 more Smart Citation